Harnessing anthocyanin-rich fruit: a visible reporter for tracing virus-induced gene silencing in pepper fruit. Issue 1 (December 2017) - Kim, Jihyun; Park, Minkyu; Jeong, Eun; Lee, Je; Choi, Doil
Abstract Background Virus-induced gene silencing (VIGS) has become a powerful tool for post-genomic technology in plant species. This is important, especially in select plants, such as the pepper plant, that are recalcitrant toAgrobacterium -mediated transformation. Although VIGS in plants has been widely employed as a powerful tool for functional genomics, scattering phenotypic effects by uneven gene silencing has been implemented in order to overcome challenges in experiments with fruit tissues. Results We improved the VIGS system based on the tobacco rattle virus (TRV) containing theAn2 MYB transcription factor, which is the genetic determinant of purple colored- or anthocyanin-rich pepper. Silencing of endogenousAn2 in the anthocyanin-rich pepper with the modified TRV vector for ligation-independent cloning (LIC) lacked purple pigment in its leaves, flowers, and fruits. Infection with TRV–LIC containing a tandem construct ofAn2 andphytoene desaturase (PDS ) resulted in a typical photobleaching event in leaves without the purple pigment, whereas silencing ofPDS led to the presence of photobleached and purple-colored leaves. Cosilencing of endogenousAn2 andcapsaicin synthase in fruits resulted in decreased levels of capsaicin and dihydrocapsaicin as assessed by high performance liquid chromatography analysis coupled with the absence of the purple pigment in fruits. Conclusions VIGS with tandem constructs harboringAn2 as a visible reporter in anthocyanin-rich pepper plants can facilitate the application of functional genomics in the study of metabolic pathways and fruit biology.